Changing interventions in farm animal health and welfare: A governmentality approach to the case of lameness. (January 2023) - Holloway, Lewis; Mahon, Niamh; Clark, Beth; Proctor, Amy
Abstract: Lameness is a significant health and welfare issue in farmed animals. This paper uses a governmentality approach, which focuses on how a problem is made governable, to examine an emerging 'ecology of devices' introduced to intervene in, and attempt to reduce, on-farm incidence of lameness. These devices are associated with advisers who work with farmers on-farm; they enact lameness as a governable entity, are tools to assess the existence of lameness against established norms, and prescribe actions to be taken in response to evidence of lameness. In doing this they subjectify farmers and advisers into seeing and responding to lameness in particular ways. Using concepts of governmentality alongside other perspectives on the power relations and the simplifications and complexities involved in interventions in animal health and farm practice, the paper draws on in-depth research with advisers including vets and other paraprofessionals who work with farmers, and their cows and sheep. It explores how this set of devices introduces particular techniques and practices in lameness management, and produces farmer and adviser subjectivities. It then explores some of the problematics of this mode of governing lameness, including analysis of the limitations and unintended consequences of attempts to simplify lameness management. The paper concludes by arguing that its approach is valuable in analysing ongoing intensification of interventions in farming practices and in understanding the limits of such interventions and the unanticipated divergences from expected conduct. Highlights: A governmentality approach to livestock lameness provides valuable insight into recent attempts to reduce its prevalence and severity on farms. The government of lameness produces farmer and adviser subjectivities linked to new tools and devices aiming to reduce the incidence of lameness. The government of lameness is limited by complexities linked with attempts to simplify interventions and deviation from expected practices.